Financial Stability Drives Fraud in Indonesian Manufacturing: Stabilitas Keuangan Mendorong Penipuan di Sektor Manufaktur Indonesia - Andini Nabila Firdaus; Heri Widodo (Academia Open, 2024)
This study investigates the influence of financial stability, external pressure, and financial targets on financial statement fraud in food and beverage manufacturing companies listed on the Indonesian Stock Exchange from 2017 to 2022. Using a quantitative approach with secondary data from 10 companies, we conducted multiple linear regression analysis with SPSS 26. Results indicate that financial stability significantly impacts financial statement fraud, while external pressure and financial targets do not. The findings suggest that improving financial stability can reduce financial statement fraud, highlighting the need for further research on the roles of external pressure and financial targets. Highlight: Financial Stability: Significantly impacts financial statement fraud. External Pressure: Does not significantly affect financial statement fraud. Financial Targets: No significant influence on financial statement fraud. Keywoard: Financial stability, external pressure, financial targets, financial statement fraud, Indonesian Stock Exchange